The Growth of Terminal Stations in the Peri-urban Areas of Bangkok Metropolis - Taeshapotiwarakun, Choochart; Tananpang, Chonmani (Journal of Ecohumanism, 2024)
The density of activities in the central Bangkok area has accelerated the development of suburban areas to reduce the density and congestion in the housing and manufacturing sectors, including various sources of employment, causing more commuters between suburbs and urban areas. Currently, traveling by train is favored as it is a convenient, fast, and timely transportation. Consequently, the public sector has extended the train route from the urban area to the suburbs of Bangkok in all directions, causing the development around the stations undoubtedly (Transit Oriented Development: TOD). Each terminal station appears diverse growth. This study aimed to examine the growth of the area surrounding the terminal stations in the peri-urban areas of Bangkok metropolis by analyzing physical changes (number of residential units), society (number of population and households), and economy (land price) in the area surrounding the terminal station extension to suburban areas which are currently distributed throughout the perimeters of the four provinces, namely Nakhon Pathom, Samut Prakan, Pathum Thani, and Nonthaburi, comprising MRT Purple Line (Khlong Bang Phai Station), BTS Green Line (Kheha Station), MRT Blue Line (Lak Song Station), and BTS Green Line (Khu Khot Station). The findings revealed that physical changes around Khu Khot Station and Khlong Bang Phai Station have constantly increased the number of residential properties from real estate projects since the construction of the stations while Kheha Station and Lak Song Station had had already a high density of ​​the former residential community, inducing a relatively low rate of increase. Regarding social changes, the population at Khu Khot Station had the highest rate of increase, and the increase in the number of households in all 4 stations did not affect the increase of households from construction to the opening. Regarding the economy, the price of waste lands around Khu Khot Station had the highest increase, followed by Kheha Station, Lak Song Station, and Khlong Bang Phai Station, respectively.